Factors Associated with the Use of Personal Protective Equipment (PPE) among Tunnel Construction Workers on Jalan Sultan Alimuddin–Jalan Kakap, Samarinda City - Sulung Alfianto Akbar (Universitas Widya Gama Mahakam Samarinda, 2015)
Based on observations and interviews with the service provider company, namely PT PP (Persero) Tbk, there were 3 minor work accidents that occurred in the work environment. Objectives: The purpose of this study was to determine the factors related to compliance with the use of personal protective equipment among tunnel construction project workers on Jalan Sultan Alimuddin to Jalan Kakap, Samarinda City in 2024. Research Metodes: The type of research used in this study is a quantitative method using a cross-sectional approach. The study was conducted in a tunnel construction project on Jalan Sultan Alimuddin to Kakap, Samarinda City. The sample used in this study was 153 respondents and based on the results of the calculation test using the Slovin formula, the sample obtained was 110 respondents. Results: The results of the study showed the availability of PPE (P value of 0.543>0.05), behavior (P value of 0.284>0.05) and length of service (P value of 0.050≤0.05) on compliance with the use of PPE among tunnel construction project workers on Jalan Sultan Alimuddin to Kakap. It can be concluded that length of service has a relationship with compliance with the use of PPE among tunnel construction project workers on Jalan Sultan Alimuddin to Kakap, which means Ha is accepted. While the availability of PPE and behavior have no relationship with compliance with the use of PPE among tunnel construction project workers on Jalan Sultan Alimuddin to Kakap, which means Ho is accepted. Conclusion: Workers are expected to be able to increase their knowledge early on, starting from the start of work, so it is hoped that workers who have minimal experience in implementing the use of personal protective equipment can understand the function of all forms of personal protective equipment in the workplace earlier.